Surface air temperature differences of intra- and inter-local climate zones across diverse timescales and climates. (15th August 2022) - Jiang, Sida; Zhan, Wenfeng; Dong, Pan; Wang, Chenguang; Li, Jiufeng; Miao, Shiqi; Jiang, Lu; Du, Huilin; Wang, Chunli
Abstract: The local climate zone (LCZ) scheme has been widely used in urban heat island studies in the past decade. However, the general principle of LCZ surface air temperature (SAT) differences and their climatic differences on different timescales remain largely unclear. Here we investigated both the inter- and intra-LCZ differences at four timescales across nine Chinese megacities characterized with significantly different climates, based on three-year hourly SAT measurements collected at 898 stations from 2017 to 2019. The results showed that (1) at the annual mean scale, the Δ T inter (i.e., SAT differences between various LCZ types and LCZ D): and Δ T intra (i.e., standard deviation of SAT measurements belonging to the same LCZ) were larger during the night than the day for most LCZ types; and the Δ T inter and Δ T intra for warm temperate cities were usually greater than those of subtropical cities. (2) At the seasonal scale, the Δ T inter and Δ T intra of most LCZs often peaked at winter night. The largest seasonal variation of Δ T inter was observed in mid-temperate cities. (3) At the daily scale, the day-to-day difference of Δ T inter was smaller during the day than the night and mainly ranged from −0.5 °C to 0.5 °C. By contrast, the day-to-day difference of Δ T intra was relatively large both during the day and night. (4) At the hourly scale, both the Δ T inter and Δ T intra variations throughout a diurnal cycle followed a characteristic U-shape for most LCZs. We consider these findings are helpful for better understanding the inter- and intra-LCZ thermal differences across various timescales and climates. Highlights: Inter- and intra-LCZ surface air temperature differences are discussed on annual, seasonal, daily, and hourly scales. Inter- and intra-LCZ SAT differences are both larger at night than during the day. Inter- and intra-LCZ SAT differences are larger in warm temperate than in subtropical cities. Inter- and intra-LCZ SAT differences reach their maxima for LCZ 1 and LCZ A, respectively.